Reading Readiness of Kindergarten Students At-Taqwa Mosque East Jakarta - Eliza, Delfi (Universitas Negeri Semarang, 2014)
This research is aimed at finding the relationship between visual and auditory perception between towards reading readiness of the second year student of Kindergarten.This research was conducted at the East Jakarta Kindergarten At-Taqwa. The samples of the research consisted of 30 students were selected by who using simple random sampling technique was used in this research. The data were collected by using visual and auditory perception test and reading readiness test. The data of the study were analyzed by Applying multiple regression and correlation techniques. The research findings that show: there is a significant correlation between visual perception towards reading readiness of the second years of At-Taqwa Kindergarten student, East Jakarta. There is a significant correlations between both visual perception and auditory perception towards reading readiness of the second years student of the East Jakarta Kindergarten At-Taqwa.How to citeEliza, D. (2015). Reading Readiness of Kindergarten Students At-Taqwa Mosque East Jakarta. Indonesian Journal Of Early Childhood Education Studies, 3(1), 1-6. doi:10.15294/ijeces.v3i1.9467